2016
DOI: 10.3892/mmr.2016.5973
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen gas plasma treatment of bacterial spores induces oxidative stress that damages the genomic DNA

Abstract: Gas plasma, produced by a short high‑voltage pulse generated from a static induction thyristor power supply [1.5 kilo pulse/sec (kpps)], was demonstrated to inactivate Geobacillus stearothermophilus spores (decimal reduction time at 15 min, 2.48 min). Quantitative polymerase chain reaction and enzyme‑linked immunosorbent assays further indicated that nitrogen gas plasma treatment for 15 min decreased the level of intact genomic DNA and increased the level of 8-hydroxy-2'-deoxyguanosine, a major product of DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Our analysis showed a reduction in the levels of CAT, DNA, and LPS in E. coli after plasma treatment. Previous studies have analyzed gas plasma [ 22 , 23 , 24 , 25 ], which led to oxidation/modification of DNA and protein as well as their degradation. LPS, also termed as endotoxin, is a component of the outer membrane of Gram-negative bacteria and is known to be highly resistant to both physical and chemical treatment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed a reduction in the levels of CAT, DNA, and LPS in E. coli after plasma treatment. Previous studies have analyzed gas plasma [ 22 , 23 , 24 , 25 ], which led to oxidation/modification of DNA and protein as well as their degradation. LPS, also termed as endotoxin, is a component of the outer membrane of Gram-negative bacteria and is known to be highly resistant to both physical and chemical treatment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that influenza virus, respiratory syncytial virus, and adenovirus are inactivated within 5 min by BLP–TES applied at 1.5 kpps [ 23 , 24 , 25 ], whereas treatment for more than 15 min is required for the inactivation of bacterial spores [ 22 ]. Overall, these findings are consistent with the notion that prion agent is a more resistant pathogen than viruses or bacteria including bacterial spores.…”
Section: Discussionmentioning
confidence: 99%
“…Our group previously reported that nitrogen gas plasma causes protein denaturation [ 21 , 22 ]. Roth et al [ 32 ] also reported the same phenomenon of protein inactivation due to oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations